A formação do gestor educacional da escola pública em ambientes virtuais de aprendizagem: trilhando caminhos na via da complexidade - Rós, Cristina Vitorino da (2009)
This academic work researches the potentiality of dialogic approach in the Theory of Complexity based on Transdisciplinarity and Ecossistemic Thought to online formation of educational manager of brazilian public schools. It is linked to RIES (Red Internacional de Ecología de los Saberes), which defends the humanist approach as an alternative to the contradictions of globalization and neoliberals practices, which is based on the high value set on the capitalistic logic and on the low value set on the citizens construction and its ethic values, as well as an holistic, happy and sustainable formation. The RIES has Ten Steps about Transdisciplinarity and Ecoformation, searching for new principles and practices to reinvent education. The research is specifically linked to the item number eight of Ten Steps, which is related to the formation of the citizens in the Knowledge Society. It starts from the principle that the formation of educational manager is in a context of structural transformations and, consequently, the traditional methods of teaching and learning need to be totally changed, considering the new opportunities offered by Technologies of Information and Communication (TIC) in the Knowledge Society. Developing a formation-research about the experience of continuous formation of educational manager in Programa Escola de Gestores, developed by a brazilian public university, this research studies how the educational manager can build the necessary knows of his profession, observing and analyzing the contribution of virtual environment on his formation, including meta cognitive process